KONSEP MOTIVASI KERJA DALAM PENGEMBANGAN KARIR ANGGOTA KEPOLISIAN - Dhela Gusti Octavia; Putri Najzwa Maulida, Sheldio Balvas Vadilla, Tri Wahyuni, Tugimin Supriyadi (Jurnal Ekonomi dan Bisnis, 2026)
The Indonesian National Police (Polri) focuses on increasing employee motivation to improve their performance. Motivation is one of the important factors that influences individual success. If the police do not have work motivation it will have a negative impact on their performance; Decreased quality of public services, decreased productivity, loss of initiative and creativity, increased absenteeism and turnover, high levels of stress and job dissatisfaction, poor work relationships. Therefore, it is important to increase motivation for police performance, various strategies have been implemented, including providing good examples, supporting the role of psychologists in the police to help police officers overcome stress and depression, providing role models, instilling discipline, and providing career development opportunities, as well as creating positive and supportive work environment. Education and training is one of the keys to enhancing career growth and mental growth and communication tactics have been researched to understand their impact on performance. Work motivation can influence a person's performance by up to 80%. High motivation is usually associated with increased productivity, work quality, and initiative. Therefore, increasing work motivation is an important factor in human resource management in various organizations, including the National Police. The aim of this research is to find out how much influence motivation has on the performance of the National Police. Involves analyzing techniques such as role modeling, instilling discipline, and providing career development opportunities.